Institutions, power, and institutional balance - Craig, P (Oxford University Press, 2021)
Institutional balance, as opposed to strict separation of powers, characterized the disposition of legislative and executive power in the EEC from the outset. The chapter is divided into four temporal periods. The initial period runs between the Rome Treaty and the Single European Act 1986 (SEA). The discussion begins with the initial disposition of institutional power in the Rome Treaty, and charts the way in which this shifted during the first thirty years. The second section covers the period between the SEA and the Nice Treaty, in which there was growing consensus in normative terms as to the appropriate disposition of primary legislative power, but continuing contestation as to power over secondary rule-making and the locus of executive authority. These tensions were readily apparent in the third period, which covers the Constitutional Treaty and the Lisbon Treaty. The fourth period runs from the advent of the Lisbon Treaty to the present. The EU has been beset by a series of crises, which had implications for the powers of the respective EU institutions and the institutional balance between them.